„Maria Magdalena powiedziała do niego po hebrajsku: «rabbuni»” (J 20,16). „Rabbuni” i inne aramejskie określenia odnoszące się do Boga/Chrystusa w greckim tekście Nowego Testamentu - Ostański, Piotr (Poznańskie Studia Teologiczne, 2018)
Everyone who studies the New Testament Bible must take into account its Aramaic backgro- und that results from several factors: – the Aramaic language was very popular in Roman Palestine during the rst century A.D.; – the Aramaic was Jesus’ mother tongue; – Jesus’ teaching was being recorded in Aramaic and then it circulated among the people; – the oldest Church consisted of Aramaic speaking communities. It is worth remembering that the New Testament authors, when working on the Greek Gospels, they were following their Aramaic language habits. The e ects of them were aramaisms in the Greek texts, Aramaic sentence constructions and even Aramaic words rendered by Greek letters. The aim of this paper was to investigate the Aramaic words referring to the God/Christ in the Greek text of the New Testament. Three Aramaic words were analysed: – Messias (John 1:41; 4:25); Greek equivalent is Christos; – Rabbouni (John 20:16; Mk 10:51); Greek equivalent is Didaskale; – Abba (Mk 14:36; Rom 8:15; Gl 4:6); Greek equivalent is ho patēr. The last term is semantically di erent from its Greek equivalent. Being derived from everyday language, it reveals the truth about God in a surprising way.